2003
DOI: 10.1620/tjem.200.203
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenol (-)-Epigallocatechin Gallate Prevents Oxidative Damage on Periventricular White Matter of Infantile Rats with Hydrocephalus

Abstract: Hydrocephalus causes damage to periventricular white matter at least in part through chronic ischemia. Emphasizing the periventricular ischemia/hypoxia in hydrocephalus, various authors indicated the secondary biochemical impairment and oxidative damage in experimentally induced and congenital hydrocephalic rat brain. (-)-Epigallocatechin gallate (EGCG), the main constituent of green tea polyphenols, has been shown to be of some protective value in various models of neurological injury as a free oxygen radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…Consistent with our previous findings, exposure to IH was associated with a significant increase in lipid peroxidation in the cortex of animals exposed to IH (18,40). In our experiments, we also observed that IH-induced increases in MDA were attenuated by GTP administration, and these findings are consistent with previous studies whereby EGCG (the most active GTP) seems to be neuroprotective against neuronal damage after global ischemia in gerbils (37) and reduces lipid peroxidation and is neuroprotective for hydrocephalus-induced periventricular oxidative damage in a rat model (35).…”
Section: Lipid Peroxidation (Mda Expression)supporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous findings, exposure to IH was associated with a significant increase in lipid peroxidation in the cortex of animals exposed to IH (18,40). In our experiments, we also observed that IH-induced increases in MDA were attenuated by GTP administration, and these findings are consistent with previous studies whereby EGCG (the most active GTP) seems to be neuroprotective against neuronal damage after global ischemia in gerbils (37) and reduces lipid peroxidation and is neuroprotective for hydrocephalus-induced periventricular oxidative damage in a rat model (35).…”
Section: Lipid Peroxidation (Mda Expression)supporting
confidence: 92%
“…Although the potential mechanisms whereby GTP may prevent neurological deficits remain to be fully elucidated, recent evidence suggests that GTP may operate as potent free oxygen radical scavengers and protect the brain and other Relative prostaglandin E 2 (PGE 2 ) production in the hippocampal CA1 region of rats exposed to room air (RA) or intermittent hypoxia (IH) and treated with green tea polyphenols (GTP) or vehicle (n 5 3 per group; *P , 0.05, # P , 0.05 vs. RA). organs from lipid peroxidation injury (35). For example, EGCG has been shown to reducing H 2 O 2 and ferrous ion-induced lipid peroxidation in gerbil brain homogenates and to inhibit lipid peroxidation in kidney and liver tissue after induction of oxidative stress with bromotrichloromethane (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we adopted the paradigm of pretreatment in an attempt to provide neonatal neuroprotection through manipulation of the maternal diet. Dietary supplementation with foods rich in polyphenols-blueberries, green tea, and apple juicehas been shown to provide neuroprotection in an animal model of focal brain ischemia, an animal model of periventricular white matter injury, and an animal model of Alzheimer's disease (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In the pathogenesis of hydrocephalus, besides the primary mechanical injury associated with ventricular dilatation, the presence of a mechanism of a secondary injury resulting from destructive and ischemic alterations in periventricular area was demonstrated both in experimentally-induced hydrocephalic animal models (3,11,14) and in congenitally hydrocephalic rats (23). It has been observed that as long as the hydrocephalic process progresses, consequent alterations emerge preferably at those areas sensitive to ischemia.…”
Section: Introductionmentioning
confidence: 99%